2021
DOI: 10.3147/jsfp.56.79
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of Lethal and Sub-lethal Toxicity of Febantel in the Juvenile Japanese Amberjack <i>Seriola quinqueradiata</i>

Abstract: Febantel (FBT) is a pro-benzimidazole anthelminthic agent. Along with its active metabolite fenbendazole (FBZ), FBT is generally considered a safe drug option to treat various parasites and is commonly used in veterinary medicine due to its efficacy, broad-spectrum activity, and ease of oral administration (Dar et al., 2017;Hardy-Smith et al., 2012). Both compounds are most often used to treat pets and livestock, including mammals, birds, reptiles, and fish (Papich, 2015). In fish, FBT and FBZ have shown effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
2
1
Order By: Relevance
“…Toxicity of FBT, however, can be an issue. Although FBT is generally considered a safe benzimidazole relative, toxicity of FBT on Seriola fish has previously shown, but only at higher dose and longer administration duration (50 mg/kg for over 14 consecutive days or over 200 mg/kg for 7 days) (Shirakashi et al, 2021a). In this study, no apparent negative effect of the drug was detected on the two Seriola species.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Toxicity of FBT, however, can be an issue. Although FBT is generally considered a safe benzimidazole relative, toxicity of FBT on Seriola fish has previously shown, but only at higher dose and longer administration duration (50 mg/kg for over 14 consecutive days or over 200 mg/kg for 7 days) (Shirakashi et al, 2021a). In this study, no apparent negative effect of the drug was detected on the two Seriola species.…”
Section: Discussioncontrasting
confidence: 52%
“…The FBT treatment at the same dose (10 mg/kg BW/d for 5 days) has been shown to be safe in Seriola spp. in other studies (Kawakami et al, 2021;Shirakashi et al, 2021aShirakashi et al, , 2021b. Therefore, this treatment regimen likely induces no or very minor, if any, toxicity to S. dumerili and S. quinqueradiata.…”
Section: Discussionmentioning
confidence: 74%
“…No clinical adverse effects were observed in the Caspian turtles in the present study. However, some studies have reported severe side effects for FNB in chelonians, including Herman's tortoise, and there are several reports of toxicity and side effects of FNB in other marine species (Doss et al, 2018; Neiffer et al, 2005; Shirakashi et al, 2021). Conversely, LVM appears safe, with no adverse effects reported after administration in red‐eared slider turtles (Corum et al, 2019) and some marine animals including common carp (Kolarova et al, 2022) and juvenile pacu (Pahor‐Filho et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study indicated lethal and sub-clinical toxicity of FBT on S. quinqueradiata when doses over 20 mg/kg body weight per day (mg/kg/d) were administered for a prolonged period (i.e. for several weeks) (Shirakashi et al, 2021). Oral administration of FBT of 3 mg/kg/d for more than 3 day was experimentally shown to be effective in treating beko disease; therefore, the normal usage of FBT should not have considerable adverse effects on Seriola fish (Kawakami et al, 2021;Shirakashi et al, 2021;Yanagi et al, 2021).…”
mentioning
confidence: 99%
“…for several weeks) (Shirakashi et al, 2021). Oral administration of FBT of 3 mg/kg/d for more than 3 day was experimentally shown to be effective in treating beko disease; therefore, the normal usage of FBT should not have considerable adverse effects on Seriola fish (Kawakami et al, 2021;Shirakashi et al, 2021;Yanagi et al, 2021). However, the precise effects of the drug on fish health should be clarified.…”
mentioning
confidence: 99%